Science or literature? the divergent cultures of discovery and creation - Maxwell, Donald R. 1929- (Lang, 2000)
Literature attempts to give utterance to the ineffable and uses ambiguity, metaphor, and the evocation of memory to create new and wonderful worlds. Science discovers that which already exists while literature creates that which might never exist. These differences are illustrated by the writings of Marcel Proust, Henri Bergson, and others."--BOOK JACKET
Keywords: Bergson, Henri <1859-1941>; Proust, Marcel <1871-1922>; Literature and science; Literatur; Methodenstreit; Wissenschaft; Exakte Wissenschaften